Experimental Study on Dynamic Mechanical Properties of Coal Gangue Concrete - Zhishu Yao; Yu Fang; Weihao Kong; Xianwen Huang; Xuesong Wang (Advances in Materials Science and Engineering)
In order to study the static and dynamic mechanical characteristics of the coal gangue concrete used in the mine support structure, the compressive strength test, the drop weight impact test, and the Split Hopkinson Pressure Bar (SHPB) test were conducted. The compressive strength, initial and final impacting energy, dynamic strength, and failure characteristic of concrete were obtained of the concrete single-doped with coal gangue coarse aggregate, single-doped with coal gangue fine aggregate, and codoped with coal gangue coarse and fine aggregates. The results show that (1) it is feasible that employing coal gangue to replace natural coarse and fine aggregates in concrete can prepare C30 and C40 concrete; (2) the addition of coal gangue fine aggregate has a positive effect on the impact energy of the initial and final cracks of concrete, while the addition of coal gangue coarse aggregate has a negative effect on it; (3) compared with the static strength, the dynamic strength of concrete is improved no matter whether coal gangue is added to concrete; (4) the incorporation of coal gangue coarse aggregate will make the concrete shear surface smooth; (5) at the given impacting pressure, the concrete with coal gangue coarse aggregate has greater particle breakage and those with coal gangue fine aggregate has less. The research of this study can be a reference for the application of gangue concrete in mine support structures.